Tubeless Percutaneous Nephrolithotomy: Spinal versus General Anesthesia - Gonen, Murat; Basaran, Betul (Urology Journal, 2014)
Abstract Purpose: Tubeless percutaneous nephrolithotomy (PCNL) with double-J stenting is a good option for large kidney calculi without increasing blood loss. In many centers tubeless PCNL is performed under general anesthesia. In the present study we evaluated the impact of spinal anesthesia in patients undergoing tubeless PCNL. Material and Methods: Between February 2011 and February 2012, forty six patients with kidney calculi were treated with tubeless PCNL. Of these patients 26 were treated under spinal anesthesia (group 1) and remaining 20 were treated under general anesthesia (group 2). Groups were compared according to patient demographics, stone size, access number, operative time, presence of supracostal access, analgesic requirement, length of hospital stay, and complications. Results: There were not any statistically significant differences between groups in terms of patient demographics, mean stone size, mean access number, operative time, presence of supracostal access, and length of hospital stay. However, the analgesic requirement was significantly less in group 1 (53 ± 39 mg vs. 111 ± 46 mg, intravenous tramadol in groups 1 and 2, respectively P < .001). Conclusion: Tubeless PCNL under spinal anesthesia is a good alternative for general anesthesia in adult patients. Spinal anesthesia decreases analgesic requirement in patients that were performed tubeless PCNL compared to general anesthesia.